2021
DOI: 10.1080/2162402x.2021.2010905
|View full text |Cite
|
Sign up to set email alerts
|

CCL5 production in lung cancer cells leads to an altered immune microenvironment and promotes tumor development

Abstract: Current immunotherapies for lung cancer are only effective in a subset of patients. Identifying tumor-derived factors that facilitate immunosuppression offers the opportunity to develop novel strategies to supplement and improve current therapeutics. We sought to determine whether expression of driver oncogenes in lung cancer cells affects cytokine secretion, alters the local immune environment, and influences lung tumor progression. We demonstrate that oncogenic EGFR and KRAS mutations, which are early events… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…Dysfunction of cytokines and chemokines (e.g., IL‐1β, IL‐6, IL‐10, CCL2, CCL5) in TME of lung cancer were able to activate the tumor cell and inflammatory cell through signal pathway family such as nuclear factor‐kappa B (NF‐κB) family and signal transducer and activator of transcription (STAT) family which may lead to tumor immune escape, tumor angiogenesis, epithelial‐to‐transition (EMT) and anti‐apoptosis in lung cancer 42–44 . In addition, CCL5 can decreased regulatory T cells (Tregs) through MAPK activation and promote an immune suppressive lung cancer environment 45 . It was reported that under the stimulation of IL‐17A, the process of migration, invasion, and EMT can be promoted by NLRP3 activation in lung cancer 46 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dysfunction of cytokines and chemokines (e.g., IL‐1β, IL‐6, IL‐10, CCL2, CCL5) in TME of lung cancer were able to activate the tumor cell and inflammatory cell through signal pathway family such as nuclear factor‐kappa B (NF‐κB) family and signal transducer and activator of transcription (STAT) family which may lead to tumor immune escape, tumor angiogenesis, epithelial‐to‐transition (EMT) and anti‐apoptosis in lung cancer 42–44 . In addition, CCL5 can decreased regulatory T cells (Tregs) through MAPK activation and promote an immune suppressive lung cancer environment 45 . It was reported that under the stimulation of IL‐17A, the process of migration, invasion, and EMT can be promoted by NLRP3 activation in lung cancer 46 .…”
Section: Discussionmentioning
confidence: 99%
“…According to RECIST v1.1, the number of patients evaluated as CR, PR, SD, or PD was 1 (2.0%), 19 (37.3%), 13 (25.5%), and 18 (35.3%), respectively. Patients were then categorized as DCB (28, 54.9%) or NDB (23,45.1%) according to the criteria described Section 2 and elsewhere. [33][34][35] The clinical features have been summarized in Table 1.…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…A higher TMB score was observed in C1, demonstrating that this subgroup might be responsive to ICB. Oncogenic mutations are usually regarded as driving factors of tumorigenesis via tumor cell-intrinsic mechanisms (35). LUAD exhibits the traits of a high mutational rate of driver genes.…”
Section: Discussionmentioning
confidence: 99%
“…Oncogenic mutations are usually regarded as driving factors of tumorigenesis via tumor cell-intrinsic mechanisms ( 35 ). LUAD exhibits the traits of a high mutational rate of driver genes.…”
Section: Discussionmentioning
confidence: 99%
“…Both CCL5 and CCL22 were associated with the recruitment of Tregs, which may induce the exhaustion of CD8+ T cells. A prominent temporal increase of CCL5 was also demonstrated in EGFR-MT through increased MAPK/ERK signaling ( 81 ). The CCL22 was also elevated in EGFR-MT via JNK/c-Jun activation ( 22 ).…”
Section: Tme In Oncogenic Driver Mutationsmentioning
confidence: 99%